An Analysys of Students’ Inference Skill toward Students’ Reading Comprehension - Supatmi, Ruri; Wiratno, Purna (STKIP PGRI Bandar Lampung, 2022)
The study of inference skill concerned with infer the message from the text which is written by the author. Studying on inference always faced the different text. Inference skill was occurred in some levels. These levels were very important to keep the meaning of the text to avoid the awkwardness. This research was aimed to find how was the student’s inference skill in reading comprehension at the sixth semester done by the students of English education study program in Universitas Nahdlatul Ulama Lampung. The characteristic of this research was qualitative research by applying Miles and Huberman models; namely collecting data, data reduction, data display and drawing conclusion. The result of the students’ inference skill in reading comprehension was done by the students of English Study Program Universitas Nahdlatul Ulama Lampung, in coherence inference, there were ten percent of students making error in this level.